2013
DOI: 10.1021/ja400015e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Odd–Even Side Chain Length of Alkyl-Substituted Diphenylbithiophenes on First Monolayer Thin Film Packing Structure

Abstract: Because of their preferential two-dimensional layer-by-layer growth in thin films, 5,5′bis(4-alkylphenyl)-2,2′-bithiophenes (P2TPs) are model compounds for studying the effects of systematic chemical structure variations on thin-film structure and morphology, which in turn, impact the charge transport in organic field-effect transistors. For the first time, we observed, by grazing incidence X-ray diffraction (GIXD), a strong change in molecular tilt angle in a monolayer of P2TP, depending on whether the alkyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 71 publications
4
63
0
Order By: Relevance
“…[19][20][21] Long-chain thiols and disulfides are used for the fabrication of SAMs especially on gold nanoparticles and two-dimensional surfaces where sulfur atom forms covalent bond with gold and the long chain of atoms help the building block of monolayers to orient at a certain angle with respect to the surface on which it is formed. [22][23][24] Two alternative methodologies are commonly followed in order to prepare the required alkanethiol or disulfide monolayers on gold nanoparticles: (a) the ligand exchange method: it is a two-step procedure where first the preparation of citrate or thiol-stabilized gold nanoparticles is done followed by displacement of the initial stabilizers with desired thiols. [25,26] tetraoctyl-ammonium bromide as a phase-transfer agent and reduced with aqueous NaBH 4 in the presence of the thiol or disulfide.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Long-chain thiols and disulfides are used for the fabrication of SAMs especially on gold nanoparticles and two-dimensional surfaces where sulfur atom forms covalent bond with gold and the long chain of atoms help the building block of monolayers to orient at a certain angle with respect to the surface on which it is formed. [22][23][24] Two alternative methodologies are commonly followed in order to prepare the required alkanethiol or disulfide monolayers on gold nanoparticles: (a) the ligand exchange method: it is a two-step procedure where first the preparation of citrate or thiol-stabilized gold nanoparticles is done followed by displacement of the initial stabilizers with desired thiols. [25,26] tetraoctyl-ammonium bromide as a phase-transfer agent and reduced with aqueous NaBH 4 in the presence of the thiol or disulfide.…”
Section: Resultsmentioning
confidence: 99%
“…The zigzag-like fluctuations in the out-of-plane d-spacing values may have resulted from the difference in the intermolecular interactions between the DPP-SVS polymer chain, the underlying selfassembled monolayer (SAM), and/or the different intermolecular packing structures. [32,38,39] For the linear alkyl chain system, mostly even-numbered alkylsubstituents have been used. [32] Additionally, crystallographic analysis of n-alkanes showed that oddnumbered n-alkanes have two molecules in the unit cell with lower density, while even-numbered n-alkanes have 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 one molecule in the unit cell with optimal intermolecular contacts in the arrangement.…”
Section: Microstructural Analysis Of Polymer Filmsmentioning
confidence: 99%
“…[32,38,39] For the linear alkyl chain system, mostly even-numbered alkylsubstituents have been used. [32] Additionally, crystallographic analysis of n-alkanes showed that oddnumbered n-alkanes have two molecules in the unit cell with lower density, while even-numbered n-alkanes have 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 one molecule in the unit cell with optimal intermolecular contacts in the arrangement. [40,41] The denser molecular packing of an even-numbered n-alkane typically requires more energy to break it apart, leading to the trend in higher melting points.…”
Section: Microstructural Analysis Of Polymer Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semiconducting π‐conjugated polymers made of donor–acceptor (D–A) hybrids are still leading the development, which show facile tuning of band gaps and energy levels by introducing new or different constituent units . However, in comparison to the development of new conjugated building blocks, modifying side chains offers an alternative, perhaps more convenient and cost‐effective route to optimize materials . Modifying side chain constituents is usually done in a framework of an established high‐performance backbone with the aim of fine tuning the morphology.…”
Section: Introductionmentioning
confidence: 99%